2017
DOI: 10.1007/s40261-017-0592-2
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Asenapine in the Treatment of Bipolar Disorder

Abstract: Bipolar disorder places a significant burden on the affected individuals, their family, healthcare systems and the overall economy. More treatment options are needed, especially those with better efficacy and tolerability. Asenapine is a second-generation antipsychotic approved in Europe (brand name Sycrest®) for the treatment of moderate-to-severe manic episodes associated with bipolar I disorder in adults, and in the US (brand name Saphris®) for the treatment of manic or mixed episodes of bipolar I disorder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…A black-cherry formulation is available to possibly lessen the unpleasant taste. 65 The etiology of the oral hypoesthesia is likely attributable to local anesthetic activity; however, the effects are typically transient and resolve within 1 h. 66 , 67 …”
Section: Tolerabilitymentioning
confidence: 99%
“…A black-cherry formulation is available to possibly lessen the unpleasant taste. 65 The etiology of the oral hypoesthesia is likely attributable to local anesthetic activity; however, the effects are typically transient and resolve within 1 h. 66 , 67 …”
Section: Tolerabilitymentioning
confidence: 99%
“…The FDA approved asenapine for the treatment of schizophrenia (331) and bipolar disorders (332) in 2019. This drug is a new AAP with unique features that was introduced in Japan in 2016, and it is the only AP used sublingually; its chemical structure of (±)-Asenapine can be described as a tetracyclic framework wherein N-methylpyrrolidine ring fuses at third and fourth positions with chlorophenyl phenyl ether in a trans geometry (333) (see Figure 1).…”
Section: Asenapinementioning
confidence: 99%
“…Asenapine displays more potent antagonist activity toward 5-HT 2A receptor than D2 receptor (337,338), that is why it has a low propensity to cause PRL elevation (331,339,340); Therefore, this drug is one of the AP treatments of choice for breast cancer patients (341). Nevertheless, research groups reported that 2.3% of patients with bipolar disorder who received asenapine monotherapy had PRL levels ≥ 4 times the upper limit of the normal range, compared with those who received a placebo (332,342), In contrast, 9% of patients with schizophrenia who received asenapine (5 and 10 mg twice daily) had PRL levels over 2-fold the upper limit of the normal range compared with those who received a placebo (343).…”
Section: Asenapinementioning
confidence: 99%
“…Asenapine is a novel atypical antipsychotic drug approved for the treatment of schizophrenia, ameliorating both positive and negative symptoms [ 24 , 25 , 26 , 27 ]. Asenapine has been also recommended for the treatment of manic/mixed episodes with or without psychotic features associated with bipolar I disorder, such as manic-depressive bipolar disorder [ 28 , 29 , 30 ]. As asenapine is a tetracyclic member of the dibenzooxepinopyrroles, derived from the tetracyclic antidepressant mianserin, it would be expected to have also an antidepressant effect [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%